PROFITABILITAS DAN RESIKO BISNIS PADA PT. BANK RAKYAT INDONESIA (PERSERO)Tbk - -, Irma Lestari (EKONOMIA, 2014)
The owner of the company particularly the management company will try to increase profits as well recognized how important advantage for the company’s future. Therefore, attention focused on profitability due to could go  on, a campany must be in a state favorable/profitable and without any advantage would be very difficult for campanies to attarack capital from outside. On the other hand there is no one who does not have a risk business.            The purpose of this study was to determine the profitability of the development of PT. Bank Rakyat Indonesia (Persero) Tbk years 2010 to 2012, and the business risks faced by PT. Bank Rakyat Indonesia (Persero) Tbk in 2010-2010.            Basic theory used is financial management by using financial ratio analysis.            Based on the analysis and discussion of the conclusions of this study are.Profitability ratios from year 2010-2012 showed an increasing trend from year to year.Business risk ratio of the 2010 – 2012 increase fluctuated.            The relationship between the profitabuility of the business risk experienced by the company can be described as follows :Credit risk from 2010 to 2011 the company increased by 13,98% indicates the company has increased its business risk but profitability especially net profit margin grew by 0,43% despite risknya capital increased by 12,03%, which means that the company increases business risk but with net growth profile 0f Rp. 3,615,611,000,000, while credit risk from 2011 to 2012 of 24.76% indicates that the company lowered the profitability of the business risk especially net profit margin grew by 1.19% despite risknya capital increased by 21.35% means that the company has increased risk, but dibarangi with net growth profile of Rp. 3,599,384,000,000, so it can be said that the increase in business risk taken by the company resulted in greater business opportunities that have an effect on improving profitability.            Based on the analysis and discussion of the hypothesis that the increased risk was also followed by an increase in the profitability of business accepted, because based on the analysis of states with increased risk thereby increasing the profitability of the business of PT. Bank Rakyat Indonesia (Persero) Tbk.